DISTRIBUTION OF ZAKAT FITRAH THROUGH SHOPEE E-COMMERCE: Digital Transformation in the Modern Era - Shofa Robbani; Sabilla Putri Khairunisa; Nidaul Mahmudah; Linda Aprillia; Latifatus Syafi'iyah; Hakim Musthofa Habibullah (JURNAL HAKAM, 2025)
This study examines the practice of zakat fitrah distribution through digital platforms, particularly marketplaces like Shopee, from the perspective of Islamic law. The phenomenon of zakat digitalization has emerged as a response to technological developments and the modern need for convenience in religious obligations. The purpose of this research is to assess the validity of such practices based on the principles of zakat jurisprudence and to identify the challenges and impacts of digital zakat fitrah implementation. This study uses a normative-juridical approach with qualitative descriptive methods, collecting data through literature review of classical and contemporary sources as well as observation of marketplace practices. The findings indicate that from an Islamic legal standpoint, online zakat fitrah distribution is permissible as long as it fulfills the elements of intention, time, zakat form, and proper distribution to eligible recipients (mustahik). However, challenges such as lack of transparency, the possibility of zakat not reaching local beneficiaries, and misuse of zakat funds remain issues. In conclusion, digital zakat fitrah is legally valid in Islam if it involves official zakat institutions and maintains accountability. This study recommends stricter oversight, public education on digital zakat, and development of location-based systems for more equitable and effective distribution.